DIPLOMASI BUDAYA INDONESIA TERHADAP TUNISIA MELALUI PENCAK SILAT - Ar Taufik Ali Totonji; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Cultural diplomacy is a form of government effort to engage in diplomatic relationship using their nation’s culture. This effort is done by introducing and expanding the information regarding their culture. In practice, cultural diplomacy is implemented through cultural activities in another nation with the goal to pull in the attention of foreigner towards said culture. Pencak Silat is one form of Indonesia’s cultural richness, thus the nations has utilized it as a tool to achieve its interest in the international stage.The perspective used in this research is the Neorealist Perspective in which this perspective assumes that the phenomenon which have happened in this world has cemented the fact that all the nations of this world is engaged with one another in some type of way. The interactions between nations have birthed a new conception that it is impossible for any one nation to fulfill its needs and interest by it lonesome. In essence nations and human is similar, in which neither can survive alone without interaction with each other.Pencak silat’s presence in Tunisia to this day continue to experience rapid development caused by both Indonesian government and citizen role in introducing culture thus making Indonesias fame to soar in said nation Keywords : Cultural Diplomacy, Pencak Silat, Indonesia, Tunisia